2001
DOI: 10.1038/ng0501-42
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to mouse cytomegalovirus is associated with deletion of an activating natural killer cell receptor of the C-type lectin superfamily

Abstract: Cytomegalovirus is the leading cause of congenital viral disease and the most important opportunistic infection in immunocompromised patients. We have used a mouse experimental infection model (MCMV) to study the genetic parameters of host/virus interaction. Susceptibility to infection with MCMV is controlled by Cmv1, a chromosome 6 locus that regulates natural killer (NK) cell activity against virally infected targets. Here, we use a positional cloning strategy to isolate the gene mutated at the Cmv1 locus. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
190
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 302 publications
(203 citation statements)
references
References 28 publications
8
190
1
3
Order By: Relevance
“…The importance of the LY49H receptor in NK cell-mediated resistance against MCMV was first revealed by classic genetic studies 25,26 and by experiments using a neutralizing LY49H-specific antibody 27 . The mechanism by which this receptor prevented disease had remained unclear.…”
Section: Box 1 | Memory In Myeloid Cells In Mammalsmentioning
confidence: 99%
“…The importance of the LY49H receptor in NK cell-mediated resistance against MCMV was first revealed by classic genetic studies 25,26 and by experiments using a neutralizing LY49H-specific antibody 27 . The mechanism by which this receptor prevented disease had remained unclear.…”
Section: Box 1 | Memory In Myeloid Cells In Mammalsmentioning
confidence: 99%
“…In a similar manner, mouse CMV (MCMV) has coevolved with its host for long enough to impact the NK receptor repertoire. NK cells from C57BL/6 (B6) mice carry a germline-encoded activating receptor, Ly49H, that specifically recognizes the MCMV-encoded protein m157 (Lee et al 2001;Arase et al 2002;Dokun et al 2001;Smith et al 2002). The MCMV model has established a critical role for NK cells in controlling host resistance to infection (Scalzo et al 1992), which is, in part, driven by recognition of m157 by Ly49H.…”
Section: Nk Cell Memory Following Mouse Cytomegalovirus Infectionmentioning
confidence: 99%
“…These genes can then be localized in linkage studies, and in certain cases, can be identified by transcription mapping and positional cloning. [32][33][34][35][36] The mouse is the experimental model of choice for this type of analysis for the following reasons: (1) the virulence status of the infectious agent, as well as the dose, and route of infection can be tightly controlled, thereby reducing microbial-induced variability; (2) large numbers of wild-type isolates and mutant stocks of mice are available in an inbred status; (3) informative segregating animals can be generated in large numbers for linkage mapping and positional cloning; (4) the sequence of the mouse genome is soon to be completed, providing a compendium of candidate genes for a particular region; (5) null alleles at candidate genes can be readily obtained by gene targeting; and (6) 37,38 The symptoms and pathology associated with blood-stage infection of mice with P. chabaudi , while not exactly mirroring those associated with human malaria, are similar enough that murine models have been useful in defining the immunological basis of some of the pathology in man (reviewed in Mohan and Stevenson 5 ). Many blood-stage antigens of this parasite are analogous to those of P. falciparum.…”
Section: A Mouse Model Of Malaria Infectionmentioning
confidence: 99%